2015
DOI: 10.4041/kjod.2015.45.6.275
|View full text |Cite
|
Sign up to set email alerts
|

Integrated three-dimensional digital assessment of accuracy of anterior tooth movement using clear aligners

Abstract: ObjectiveTo assess the accuracy of anterior tooth movement using clear aligners in integrated three-dimensional digital models.MethodsCone-beam computed tomography was performed before and after treatment with clear aligners in 32 patients. Plaster casts were laser-scanned for virtual setup and aligner fabrication. Differences in predicted and achieved root and crown positions of anterior teeth were compared on superimposed maxillofacial digital images and virtual models and analyzed by Student's t-test.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…Few articles are available in the literature regarding torque movements with clear aligners [ 7 , 10 , 11 , 27 , 28 ]. Torque movement requires the presence of a force couple acting on the tooth, and the biomechanics of this type of tooth movement was described by Hahn et al [ 10 ]: the movement inside each aligner determines that initially the aligner does not fit the tooth crown perfectly, and a certain amount of reversible deformation is present at the gingival margins of the aligner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few articles are available in the literature regarding torque movements with clear aligners [ 7 , 10 , 11 , 27 , 28 ]. Torque movement requires the presence of a force couple acting on the tooth, and the biomechanics of this type of tooth movement was described by Hahn et al [ 10 ]: the movement inside each aligner determines that initially the aligner does not fit the tooth crown perfectly, and a certain amount of reversible deformation is present at the gingival margins of the aligner.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by Elkholy et al [ 29 ] measuring the moment/force (M/F) ratio produced during the bodily movement of an upper central incisor with a different aligner thickness and amount of movement for each aligner; the authors found that the M/F ratio was not large enough to produce an effective counter-movement in any of the situations studied. Zhang et al [ 28 ] combined information from digital models and cone-beam CT images to evaluate both crown and root position during anterior teeth movements. Interestingly, the authors found a large amount of crown movement and a small amount of root movement, suggesting that clear aligners are capable of mainly crown tilting movements.…”
Section: Discussionmentioning
confidence: 99%
“…These models offer several advantages, including easy storage and the possibility of computerized data acquisition and modeling. 4 5 6 7 8 9 Digital impression methods performed using intraoral scanners also completely eliminate the conventional impression-taking process using impression materials. Additionally, they reduce the gag reflex of the patient and are more comfortable, as breathing is freely permitted during the impression-taking process.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has also been confirmed by some other studies on prediction of surgical treatment outcome and outcome of treatment with clear aligners. 6,10,[30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%